The effects of annatto tocotrienol on body composition and serum adiponectin, leptin and glucose level in a rat model of androgen deficiency induced by buserelin - Mohamad NV,; Ima-Nirwana Soelaiman,; Chin, Kok Yong (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Androgen ablation therapy using gonadotropin-releasing hormone agonists is reported to be associated with metabolic abnormalities. Annatto tocotrienol (AnTT) is reported to reduce the expression of genes related to adipogenesis but the mechanism remains elusive. This study sought to determine the effects of annatto tocotrienol on body composition (lean and fat mass), serum adiponectin, leptin, and glucose levels in male rats treated with buserelin, a testosterone ablation agent. Three-month-old male Sprague Dawley rats (n=32) were randomly divided into four groups. The normal control (n=8) was given corn oil orally daily and normal saline subcutaneously daily. The remaining groups were injected with buserelin subcutaneously (75µg/kg/day). The buserelin group (n=8) was given corn oil orally, while the treatment groups were supplemented orally with AnTT at 60 or 100 mg/ kg (n = 8/group). After treatment of 12 weeks, rats were euthanized. Dual-energy x-ray absorptiometry was performed to determine the lean and fat mass of the rats. Blood was collected for the evaluation of adiponectin, leptin and glucose levels. After 12 weeks, the lean mass, fat mass, adiponectin and leptin levels for all groups increased significantly compared to their respective baseline levels irrespective of their treatment (P<0.05). All groups, except rats receiving AnTT at 60 mg/kg, experienced a significant increase in glucose level after 3 months (P<0.05). Androgen ablation and AnTT do not influence body composition, adiponectin and leptin levels in male rats. However, annatto tocotrienol at 60 mg/kg may improve glucose metabolism.